Fat?/?Hippo pathway regulates the progress of neural differentiation signaling in the Drosophila optic lobe. - Kawamori, H.; Tai, M.; Sato, M.; Yasugi, T.; Tabata, T. (Development, Growth and Differentiation, 2011)
A large number of neural and glial cell species differentiate from neuronal precursor cells during nervous system development. Two types of Drosophila optic lobe neurons, lamina and medulla neurons, are derived from the neuroepithelial (NE) cells of the outer optic anlagen. During larval development, epidermal growth factor receptor (EGFR)/Ras signaling sweeps the NE field from the medial edge and drives medulla neuroblast (NB) formation. This signal drives the transient expression of a proneural gene, lethal of scute, and we refer to its signal array as the "proneural wave," as it is the marker of the EGFR/Ras signaling front. In this study, we show that the atypical cadherin Fat and the downstream Hippo pathways regulate the transduction of EGFR/Ras signaling along the NE field and, thus, ensure the progress of NB differentiation. Fat/Hippo pathway mutation also disrupts the pattern formation of the medulla structure, which is associated with the regulation of neurogenesis. A candidate for the Fat ligand, Dachsous is expressed in the posterior optic lobe, and its mutation was observed to cause a similar phenotype as fat mutation, although in a regionally restricted manner. We also show that Dachsous functions as the ligand in this pathway and genetically interacts with Fat in the optic lobe. These findings provide new insights into the function of the Fat/Hippo pathway, which regulates the ordered progression of neurogenesis in the complex nervous system.